Evaluation of the Efficiency of Three Different Obturation Techniques to Obturate the Isthmus Area of Roots Canals Prepared by Two Different Instrumentation Techniques (An In Vitro Study) - Hasan M Al-Rammahi; Hussain F Al-Huwaizi (College of Dentistry/ University of Baghdad, 2016)
Background: The isthmus is a difficult area in the root canal complex to manage. The research aimed to evaluate the efficiency of three different obturation techniques (lateral condensation, EandQ (thermoplasticized gutta percha system) and Soft Core (thermoplasticized core carrier gutta percha system)) to obturate the isthmus area of roots prepared by two different instrumentation techniques (rotary ProTaper universal and ProTaper Next systems). Material and method: Sixty freshly extracted teeth were randomly divided into two main groups (A and B) of 30 teeth each. Group A was prepared by rotary ProTaper Universal whereas group B was prepared by ProTaper Next system. Each main group was then randomly subdivided into three subgroups of 10 teeth each, to be obturated with the three obturation techniques. All specimens were then placed in cold cure acrylic mold just from the side of the crown leaving the root unmolded to facilitate the sectioning process, then three sections were obtained from each specimen by using microtome at 2, 6 and 10 mm from the apex. Each section was viewed under stereomicroscope(40X) and imaged with digital camera(4X). Each image was managed with image J program to calculate the surface area of the whole isthmus and that of the gutta percha and/or sealer extended into the isthmus so the collected data represented the percentage of extension degree of gutta percha and /or sealer into the isthmus(EDGS). Results: The highest mean value of (EDGS) was evident with Soft Core technique in the apical area and was significantly higher than that of the EandQ and lateral condensation techniques. Conclusion: Under the conditions of this study, Soft Core system showed a higher efficiency in obturating the isthmus area than the other obturation techniques.